IMPROVEMENT OF WATER-BASED INTERIOR DYES PREPARED BY USING NATURAL MINERAL AND FIBER INDUSTRIAL PLANT - Gures, Sinem; Cifte, Tugba; Acarali, Nil; Ozturk, Abdullah Bilal; Kandilci, Hava Gizem; Ozgunduz, Hediye Irem; Sarac, Hanifi (YILDIZ TECHNICAL UNIV, 2016)
In this study, natural minerals and industrial fibrous plant waste were supplied from various regions of Turkey unlike from the literature. Dye application was carried out with 200 mu m applicator on standard sizes (10 cm x 10 cm) of metal surfaces. The dyed this original mixture was applied on the block and panel building materials. Dyes were examined according to the features of unaffected by water, not changed the nature and physical strength, high concealer effect in detail. As a result, the optimum process parameters (for two different natural minerals and the amount of industrial fibrous plant waste) were determined. The statistical method was used and the results obtained were analyzed comparatively in terms of improving both cost and quality for determination of optimum process parameters. In conclusion, the test results (concealer property, hydrophobicity, impact and adhesion tests) and results showed that the usage of natural minerals and industrial fibrous plant waste effected the production of insulated interior dye, positively.
Keywords: Dye; waste; mineral; insulation; THERMAL INSULATION MATERIALS; TEXTILE WASTE; Engineering